A case of anorexia nervosa with comorbid Crohn's disease: Beneficial effects of anti‐TNF‐α therapy?. Issue 6 (27th June 2013) - Solmi, Marco; Santonastaso, Paolo; Caccaro, Roberta; Favaro, Angela
ABSTRACT This case report describes a 26‐year‐old woman affected by long‐lasting anorexia nervosa (AN) and Crohn's disease. Worsening of the bowel illness led to the prescription of immunosuppressive therapy (biologic infliximab for 4 months, followed by adalimumab for 6 months) and referral to our Eating Disorders Unit. Although she initially demonstrated denial of her eating disorder, in a few months she gradually improved her weight and psychopathology. Crohn's disease can worsen AN by modifying hunger and energy expenditure through the effects of TNF‐α and IL‐6, pro‐inflammatory cytokines which moderate leptin and melanocortin signaling. Previous studies have observed the antidepressant effects of TNF antagonist in patients with treatment‐resistant depression with high baseline inflammatory biomarkers. Our case report suggests that future studies are needed to clarify the existence, patterns, and extent of increased inflammatory markers in patients with AN, and whether they determine clinical features or identify subgroups of patients. Potential therapeutic significance of above issues remains to be determined. © 2013 Wiley Periodicals, Inc.(Int J Eat Disord 2013; 46:639–641)